Effects of Lead Acetate on Platelet Aggregation, Ultrastructure and Serotonin Release - Davis, R. B; Holtz, G. C (Thrombosis and Haemostasis, 1971)
The effects of lead on blood platelet function and ultrastructure have been investigated. Lead acetate was injected intravenously in 27 rats and was added to rat and human platelet rich plasma in vitro. In vitro studies showed that concentrations of 2.5 × 10-3 M lead acetate reduced or blocked aggregation of rat and human platelets by adenosine diphosphate, collagen, and thrombin. Radioactive serotonin release from human platelets was inhibited by 10-4 M lead acetate. One hour after the injection of lead, platelet aggregation by thrombin was reduced, but platelet aggregation by adenosine diphosphate and collagen showed little change. Three days after lead, aggregation of platelets by collagen and thrombin was blocked and aggregation by adenosine diphosphate reduced. Thrombocytopenia was present 4 days after intravenous lead acetate. Electron micrographs of platelets showed that the mean number of mitochondria per platelet was increased, whereas alpha granules were reduced. Dense bodies were not significantly changed. Lead acetate affects platelet function in concentrations reported in human bone marrow in lead poisoning, and may relate to the binding of free sulfhydryl groups by lead.